Eine hebräisch-ägyptische Parallele für das Lob von Göttern durch Bäume - Bojowald, Stefan (Biblische Notizen, 2024)
In this contribution, a further parallel between the Hebrew and Egyptian literature is pointed out. The praise of gods by trees will be of crucial importance. The phenomenon can be demonstrated by three Hebrew and two Egyptian text passages.